Written Corrective Feedback Effects On Developing Students' Writing Capacities: The Case Of Second Year Students Of English At The University Of Annaba-algeria - Djeribiai, Adel (University of Eloued جامعة الوادي, 2017)
Responding to student writing is an important aspect of English as a Foreign Language (EFL) composition research. Error feedback on writing, in particular is still an issue of lively debate. Many researchers argued for the ineffectiveness of error correction and claimed that it is harmful and should be abandoned. Others however, have completely different views asserting that feedback is helpful in developing the writing skill. The research that we have conducted is an attempt to investigate the effectiveness of the written feedback provided by the teachers of English at Annaba University, Algeria, to the students' writing and questioning the type of feedback being delivered as well as students' perception and preferences about this feedback. The hypothesis which is put forward in this research states that the written feedback does have a positive effect on the students' writing abilities. The research makes use of questionnaires administered to teachers and learners of English in order to get a deeper understanding of the phenomenon in question. These questionnaires are followed by interviews conducted with both teachers and students of second year. In addition, an attempt has been made to describe and assess the written feedback in some corrected papers. The findings of the research have important implications for EFL writing teachers especially in developing their own techniques in providing suitable feedback which requires time and effort on the teachers' part and which ultimately would help the student writers improve their writing capacities. تعتبر الردود التي يتلقاها الطلبة حول تعابيرهم الكتابية مظهرا مهما وجوهريا في األبحاث المتعلقة باللغات األجنبية.وال يزال موضوع تصحيح أخطاء التعبير الكتابي بصفة خاصة من المواضيع المثيرة للجدل . موضوع بحثنا يتمثل في محاولة دراسة فعالية التغذية االسترجايية المكتوبة التي يقدمها أساتذة اللغة االنجليزية في جامعة عنابة للتعبير الكتابي للطلبة, ومحاولة فهم نوع التغذية االسترجايية المكتوبة, وكذا مدى ادراك الطلبة لهذه المالحظات وميوالتهم لها. تنص الفرضية الموضوعة في هذا البحث على أن المالحظات المكتوبة لها أثر ايجابي في تطوير قدرات الطلبة في التعبير الكتابي .سنستعين في البحث باستبيانين موجهين لطلبة وأساتذة اللغة االنجليزية لنتعمق في فهم الظاهرة المدروسة عالوة على ذلك سنسعى إلى تحليل المالحظات في االمتحانات المصححة.وسيكون للنتائج المتوقعة دور هام ألساتذة اللغة االنجليزية السيما في تطوير تقنياتهم الخاصة بهم وذلك بتزويدهم بمالحظات كتابية مالئمة والتي تتطلب وقتا وجهدا كبيرين من جهة األستاذ والتي قد تساعد الطلبة في تحسين قدراتهم الكتابية.
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: written feedback, composition, writing capacities, EFL; التغذية االسترجاعية المكتوبة، التعبير الكتابي، الكفاءات الكتابية، اللغات االجنبية